2015
DOI: 10.1007/s10815-015-0553-8
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana, phytocannabinoids, the endocannabinoid system, and male fertility

Abstract: Marijuana has the highest consumption rate among all of the illicit drugs used in the USA, and its popularity as both a recreational and medicinal drug is increasing especially among men of reproductive age. Male factor infertility is on the increase, and the exposure to the cannabinoid compounds released by marijuana could be a contributing cause. The endocannabinoid system (ECS) is deeply involved in the complex regulation of male reproduction through the endogenous release of endocannabinoids and binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 122 publications
(204 reference statements)
1
87
0
6
Order By: Relevance
“…Among men, the prevalence of past-year marijuana use has nearly doubled in recent years (Hasin et al, 2015). Several studies have demonstrated negative effects of marijuana use on male reproductive health, particularly decreased semen quality (Battista et al, 2008; du Plessis et al, 2015; Fronczak et al, 2012; Rossato et al, 2008). Further, marijuana use has been reported to increase the risk of testicular germ cell tumors (TGCT) (Daling et al, 2009; Lacson et al, 2012; Trabert et al, 2011), in particular, nonseminomatous TGCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among men, the prevalence of past-year marijuana use has nearly doubled in recent years (Hasin et al, 2015). Several studies have demonstrated negative effects of marijuana use on male reproductive health, particularly decreased semen quality (Battista et al, 2008; du Plessis et al, 2015; Fronczak et al, 2012; Rossato et al, 2008). Further, marijuana use has been reported to increase the risk of testicular germ cell tumors (TGCT) (Daling et al, 2009; Lacson et al, 2012; Trabert et al, 2011), in particular, nonseminomatous TGCT.…”
Section: Introductionmentioning
confidence: 99%
“…Marijuana may be related to reproductive health because of changes in circulating hormones, through tetrahydrocannabinol (THC), the principal active component of marijuana, which binds to cannabinoid system receptors (du Plessis et al, 2015). THC has been shown to have a pronounced regulatory effect on the hypothalamic-pituitary-gonadal axis (Hillard, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are yet no conclusive certainties about this phenomenon during the years, different factors have been proposed to be involved in the accumulation of risk factors for infertility and for male infertility. These factors could be either related to social changes as well as to lifestyle [47,48], such as smoke of tobacco [49][50][51] and marijuana [52][53][54], alcohol [55,56], medications [57] and caffeine [58], but also to the environmental pollution, such as pesticides, solvents [59,60], electromagnetic fields (EMFs) [61][62][63] and compounds able to interfere with the endocrine control of biological functions.…”
Section: Gscs Spermatozoa and Endocrine Disruptorsmentioning
confidence: 99%
“…During the last decade, the significance of endocannabinoid system (ECS) to both female and male fertility has been more evident (Bari, Battista, Pirazzi, & Maccarrone, ; Rossato, Pagano, & Vettor, ). Several endocannabinoids have been identified; arachidonoylglycerol ether, virodhamine, N‐arachidonoylethanolamine (or anandamide, (AEA) and 2‐arachidonoylglycerol (2‐AG)) (du Plessis, Agarwal, & Syriac, ). AEA and 2‐AG are the best‐characterised members as well as the major variants in the human body (Battista et al, ; Cacciola et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cannabinoid receptors were presented in hypothalamic regions that regulate the gonadotrophic releasing hormone (GnRH) production and may act through the hypothalamus-pituitary-gonadal (HPG) axis as well. The endogenous cannabinoid ligand, AEA, has been related to serum LH and testosterone levels in rats (du Plessis et al, 2015;Wenger, Ledent, Csernus, & Gerendai, 2001). In addition, AEA is present in human seminal plasma (Amoako et al, 2013;Schuel, Burkman, Lippes, Crickard, Forester, et al, 2002), and spermatozoa are exposed to this ligand in the epididymis (Schuel, Burkman, Lippes, Crickard, Mahony, et al, 2002).…”
mentioning
confidence: 99%